2014
DOI: 10.1177/2333392814533659
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Increases Gait Speed in Patients With Chronic Lung Diseases

Abstract: Introduction:Gait speed provides an integrated index of physical performance; changes in gait speed could reflect deterioration in the underlying medical disorder or a response to medical/surgical interventions. Slower gait speeds reflect the overall level of impairment, especially in patients with chronic lung disease.Methods:We retrospectively reviewed the medical files of 119 patients who completed the pulmonary rehabilitation program at the University Medical Center in Lubbock, Texas, and collected demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Of four randomised trials, three tested the effectiveness of exercise-based interventions (a hospital-based pedal exercise intervention, 45 pulmonary rehabilitation with or without electrical muscle stimulation, 46 and home-based pulmonary rehabilitation 47 ); one trial tested whether the severity of respiratory disability affected outcomes of centre-or homebased pulmonary rehabilitation. 48 Of 12 cohort studies, most assessed the impact of pulmonary rehabilitation on frailty or frailty components, [49][50][51][52][53][54] three assessed the feasibility or outcomes of geriatric rehabilitation, [55][56][57] and three assessed how baseline characteristics (e.g. dyspnoea severity, exercise tolerance, frailty) affect pulmonary rehabilitation outcomes.…”
Section: Focus Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of four randomised trials, three tested the effectiveness of exercise-based interventions (a hospital-based pedal exercise intervention, 45 pulmonary rehabilitation with or without electrical muscle stimulation, 46 and home-based pulmonary rehabilitation 47 ); one trial tested whether the severity of respiratory disability affected outcomes of centre-or homebased pulmonary rehabilitation. 48 Of 12 cohort studies, most assessed the impact of pulmonary rehabilitation on frailty or frailty components, [49][50][51][52][53][54] three assessed the feasibility or outcomes of geriatric rehabilitation, [55][56][57] and three assessed how baseline characteristics (e.g. dyspnoea severity, exercise tolerance, frailty) affect pulmonary rehabilitation outcomes.…”
Section: Focus Of Included Studiesmentioning
confidence: 99%
“…To maximise outcomes of exercise-based interventions, authors suggested being inclusive of people with lower baseline scores and high potential for improvements. 51,58,66 However, an inclusive stance needed to be balanced with evidence that low exercise tolerance or severe breathlessness can hinder benefit in some circumstances. 48,59 Professional stakeholders acknowledged tensions between lower baseline abilities and judging potential to benefit from services like outpatient pulmonary rehabilitation, especially when completion rates are used as a measure of service "quality".…”
Section: Factors Affecting Participation and Outcomesmentioning
confidence: 99%
“…This means that gait speed increased by at least 0.17 m/s, which is greater than the minimum clinical difference of 0.11 m/s in gait speed for 4MGS ( 56 ). There are also a small number of patients with COPD whose gait speed increases less than the minimum clinical difference value after PR; however, this does not prevent patients from benefiting from PR because it may improve survival outcomes ( 56 , 57 ). In short, these frail COPD patients can benefit from a comprehensive PR program that includes walking as an exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Gait assessment may be of clinical value as gait abnormalities have been reported in patients with COPD, including reduced cadence, reduced stride length and increased double support time as compared to healthy subjects [3,4,5,6,7]. Though PR has proven to increase gait speed in patients with COPD [39], a comprehensive analysis of gait characteristics after PR is lacking. In the current study, patients with COPD improved their walk distance during the GRAIL-based 6MWT after PR, which also reached a clinically significant improvement [26].…”
Section: Discussionmentioning
confidence: 99%